PENGARUH DIMENSI KEPRIBADIAN THE BIG FIVE PERSONALITY TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Ria Lestari Pangastuti (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2018)
The reasearch aim is for analizing the influence of personality dimension “The Big Five Personality” towards ORGANIZATIONAL Citizenship Behavior (OCB) (Studi Case Of Student Affairs Employees At X University). Population of this research is all employees of X University and sample is the employees who are at student affairs unit (50 people). The data were collected by sharing the quesioner to 50 respondents. The analysis of this research is Partial Least Square Structural EQUTION Model (PLS-SEM). Analysis result of PLS-SEM is there is significant influence of personality dimension, “The Big Five Personality” among five personality dimensions, alturism has the highest significance.